In Pursuit of Fairness? Infrastructure Investment in Digital Markets - Tobias Kretschmer (Center for Economic Studies and ifo Institute (CESifo), 2022)
Recent and ongoing investments into telecommunications infrastructure have facilitated the repeated waves of digitization, both in personal and professional life. I address the question of which actors should contribute to investment costs into telecoms infrastructure and how. One widely discussed proposal (made, for example, by ETNO, the European Telecom Network Operations' Association) is to mandate a few select large firms that offer complementary applications and services through the telecom infrastructure to compensate infrastructure providers by way of a lump sum. I discuss and evaluate this proposal from the perspectives of incentives, risk sharing, fairness, and implementability. Given the undisputed positive external effects of infrastructure investments on different actors in the internet ecosystem, I outline two theoretical first-best solutions and argue that the current proposal from ETNO is far from realizing the potential benefits of these options.
Keywords: L40; L86; L96; 330; telecommunications infrastructure; investment; OTTs